2010
DOI: 10.1088/0957-4484/21/14/145103
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between sub-10-nm iron and cerium oxide nanoparticles and 3T3 fibroblasts: the role of the coating and aggregation state

Abstract: Recent nanotoxicity studies revealed that the physico-chemical characteristics of engineered nanomaterials play an important role in the interactions with living cells. Here, we report on the toxicity and uptake of cerium and iron oxide sub-10-nm nanoparticles by NIH/3T3 mouse fibroblasts. Coating strategies include low-molecular weight ligands (citric acid) and polymers (poly(acrylic acid), M(W) = 2000 g mol(-1)). Electrostatically adsorbed on the surfaces, the organic moieties provide a negatively charged co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
66
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 49 publications
19
66
1
3
Order By: Relevance
“…These findings indicate a normal mitochondrial activity for the cultures tested. The results on the precipitated γ-Fe 2 O 3 are in good agreement with earlier reports [20,21]. As mentioned before, for this system most of the NPs were precipitated into large clusters that were not internalized because of their size (> 10 µm), but rather adsorbed on the plasma membranes.…”
Section: Mtt Toxicity Assayssupporting
confidence: 92%
“…These findings indicate a normal mitochondrial activity for the cultures tested. The results on the precipitated γ-Fe 2 O 3 are in good agreement with earlier reports [20,21]. As mentioned before, for this system most of the NPs were precipitated into large clusters that were not internalized because of their size (> 10 µm), but rather adsorbed on the plasma membranes.…”
Section: Mtt Toxicity Assayssupporting
confidence: 92%
“…These results are in agreement with previous studies reporting endocytosis of CeO 2 nanoparticles into cells. 34,35 These results indicate that CeO 2 nanoparticles have good biocompatibility at the tested concentrations and their presence inside the cells did not influence the production of the cytokines studied.…”
mentioning
confidence: 68%
“…This possibility is supported by the shift that we observed in the oxidation state of the NPs in the cellular environnment. Studies using CNPs that were synthesized by heating in solvent methods, such as the method used to generate the NPs in our study, have mostly reported either no effects [2327], or harmful effects in vitro [1,2,5], including DNA damage and oxidative stress, and in vivo [3,8,9], including lung inflammatory and injury in the rat and mouse models. Our observations are consistent with these reports, showing membrane damage but no cell death even at high doses and concentration- and time-dependent decrease and increase in oxidative stress, adding to the overall understanding that CNPs synthesized by such methods should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…These disparate effects have been linked, in part, to the NP synthesis methods and the resulting physicochemical properties of the NPs, including their oxidation state, described as the Ce 3+ /Ce 4+ ratio [21]. Harmful or no effects have been mostly reported for CNPs synthesized by high temperature and heating in solvent methods [1,2,49,2227], whereas no or beneficial effects have been reported for CNPs synthesized by room temperature methods [2838]…”
Section: Introductionmentioning
confidence: 99%